2020
DOI: 10.1093/mnras/staa1299
|View full text |Cite
|
Sign up to set email alerts
|

What causes the fragmentation of debris streams in TDEs?

Abstract: A tidal disruption event (TDE) occurs when a star passes too close to a supermassive black hole and gets torn apart by its gravitational tidal field. After the disruption, the stellar debris form an expanding gaseous stream. The morphology and evolution of this stream are particularly interesting as it ultimately determines the observational properties of the event itself. In this work, we perform 3D hydrodynamical simulations of the TDE of a star modelled as a polytropic sphere of index γ = 5/3 and study the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Most recently Bonnerot et al (2022) used a Lagrangian technique to model the evolution of the debris stream from the initial destruction of the star to the return of the most bound debris, using the frozen-in approximation for the initial conditions (Kochanek 1994 used the affine-star model of Carter & Luminet 1983 to establish the initial conditions to solve his equations of motion). Coughlin & Nixon (2015), who numerically simulated the debris stream evolution from the canonical TDE with the SPH code - (Price et al 2018), found that the stream would fragment under its own self-gravity into localized knots (see also Hayasaki et al 2020;Sacchi et al 2020), which was not predicted by earlier models (Guillochon et al 2014b argued that the combination of radiative cooling and Kelvin-Helmholtz instability could result in the formation of a clump, and did not account for the stream self-gravity in their simulations). Using their Eulerian and semi-analytical model described above, Coughlin et al (2016b) argued that the ability of the stream to fragment under its own self-gravity is critically related to its equation of state.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently Bonnerot et al (2022) used a Lagrangian technique to model the evolution of the debris stream from the initial destruction of the star to the return of the most bound debris, using the frozen-in approximation for the initial conditions (Kochanek 1994 used the affine-star model of Carter & Luminet 1983 to establish the initial conditions to solve his equations of motion). Coughlin & Nixon (2015), who numerically simulated the debris stream evolution from the canonical TDE with the SPH code - (Price et al 2018), found that the stream would fragment under its own self-gravity into localized knots (see also Hayasaki et al 2020;Sacchi et al 2020), which was not predicted by earlier models (Guillochon et al 2014b argued that the combination of radiative cooling and Kelvin-Helmholtz instability could result in the formation of a clump, and did not account for the stream self-gravity in their simulations). Using their Eulerian and semi-analytical model described above, Coughlin et al (2016b) argued that the ability of the stream to fragment under its own self-gravity is critically related to its equation of state.…”
Section: Introductionmentioning
confidence: 99%